Strategi Pemulihan Objek Wisata Lalassa Kabupaten Pandeglang - Deni Rachman Hakim; Astri Mutia Ekasari; Bambang Pranggono (Bandung Conference Series: Urban & Regional Planning, 2026)
Abstract. Lalassa is a tourist attraction as well as the main activity center of the Tanjung Lesung Special Economic Zone (KEK). This destination has consistently attracted large numbers of visitors and has even received several awards from the Anugerah Pesona Pariwisata (APP) in Pandeglang Regency. However, the 2018 Sunda Strait tsunami greatly affected the surrounding coastal areas, including the Lalassa tourist attraction within the Tanjung Lesung area. This was further compounded by the COVID-19 pandemic, which restricted population mobility and consequently led to a decline in tourist numbers. Current field observations indicate that tourism activity at the site appears quiet, with almost no visitors at certain times. Therefore, the purpose of this research is to formulate a marketing strategy for the Lalassa tourist attraction, with the expectation that this strategy can restore or increase visitor numbers. The research approach used is qualitative with a descriptive research design, while the analytical methods applied include segmentation analysis, targeting analysis, and the 4E marketing mix analysis. The findings of the study reveal several marketing strategies, namely: omni-channel marketing (offline + online), Word of Mouth and reputation strategy, Community-Based Tourism strategy, Green Marketing strategy, collaboration and partnership strategy, Branding and Positioning strategy, Smart Tourism experience strategy, marketing through accessibility and infrastructure, and promotional marketing. Abstrak. Lalassa merupakan suatu obyek wisata sekaligus pusat aktivitas dari KEK Tanjung Lesung. Obyek wisata ini selalu ramai pengunjung hingga mendapatkan beberapa penghargaan dari ajang Anugerah Pesona Pariwisata (APP) di Kabupaten Pandeglang. Namun adanya fenomena tahun 2018 yaitu terjadinya bencana tsunami Selat Sunda yang berdampak pada sekitar pesisir pantai, termasuk didalamnya obyek wisata Lalassa dari Kawasan Tanjung Lesung, Ditambah dengan adanya fenomena covid-19 yang membatasi mobilitas penduduk, sehingga hal ini berdampak pada penurunan jumlah wisatawan, hingga saat ini berdasarkan observasi lapangan menunjukkan bahwa aktivitas wisata di lokasi tersebut tampak sepi bahkan nyaris tidak terdapat pengunjung pada waktu-waktu tertentu. Maka tujuan dari penelitian ini adalah tersusunnya suatu strategi pemasaran pada obyek wisata Lalassa, harapannya strategi ini dapat memulihkan atau meningkatkan jumlah kunjungan. Pendekatan penelitian yang digunakan adalah kualitatif dengan jenis penelitian deskriptif, sedangkan metode analisis menggunakan analisis segmentasi, analisis targeting dan analisis bauran 4E. Dari hasil kajian terdapat beberapa strategi pemasaran yaitu strategi pemasaran omni channel (offline + online), strategi Word of Mouth dan reputasi, strategi Community Based Tourism, strategi Green Marketing, strategi kolaborasi serta kemitraan, strategi Branding dan Positioning, strategi pengalaman Smart Tourism, strategi pemasaran melalui aksesibilitas dan infrastruktur, dan strategi pemasaran melalui promosi.